Resolving new and old phosphorus source contributions to subsurface tile drainage with weighted regressions on discharge and season. Issue 1 (7th January 2023) - Osterholz, William; Shedekar, Vinayak; Simpson, Zachary; King, Kevin
Abstract: Agricultural losses of dissolved reactive phosphorus (DRP) emanate from both historic P applications (i.e., "old P") and recently applied fertilizer (i.e., "new P"). Understanding the relative contributions of these sources is important for mitigating DRP losses from agriculture. This study provides a proof‐of‐concept for resolving new P vs. old P source contributions to DRP losses in subsurface tile drainage using edge‐of‐field water quality data and management records from eight fields in Ohio. Weighted regressions on discharge and season (WRDS) were fitted using data from periods without P fertilizer applications and then used to predict DRP losses in tile drainage during new P loss risk periods (default length, 90 d) after fertilizer applications. Differences between observed and predicted DRP concentrations during the new P loss risk period were attributed to the new P source. Remaining losses were attributed to the old soil P source. The WRDS model performance was modest (modified Kling–Gupta efficiency ranged from −0.074 to 0.484). New P sources contributed between 0 and 17% of overall DRP losses (average, 7%), with old soil P contributing 83–100%. Individual P fertilizer applications were associated with new DRP losses up to 192 g P ha −1 . Increasing the length of the risk period for new P losses up to 180 d after fertilizer application marginally increased the estimated contribution of the new P source. The WRDS‐based analysis provides a novel approach for resolving the contributions of new and old sources to edge‐of‐field DRP losses. Core Ideas: Relative contributions of new P fertilizer applications and old soil P to tile drain DRP losses are uncertain. A novel weighted regression‐based model enabled analyzing edge‐of‐field data to estimate DRP source contributions. Reasonable estimates of DRP source contributions were obtained, with new P accounting for 0–17% of DRP losses. Sensitivity analysis indicated most new P losses occurred within 90 d after fertilization.